Formation of iron oxide and iron sulfide at high temperature and their effects on corrosion. (1st May 2018) - Gao, Shujun; Brown, Bruce; Young, David; Singer, Marc
Highlights: An inner thermodynamic less stable Fe3 O4 layer was found in high temperature H2 S corrosion. Iron sulfide polymorphs transformation at high temperature was observed for the first time. Different iron sulfide polymorphs have different roles in corrosion. Abstract: Recent high temperature H2 S corrosion study reported that a thermodynamically less stable iron oxide layer can also form in addition to iron sulfide. In this work, H2 S corrosion experiments were conducted at 120 °C for different exposure times, ranging from 1 to 21 days. The inner layer was identified by Transmission Electron Microscopy (TEM) as Fe3 O4 (magnetite); Fe3 O4 was always present over time despite it being less stable than iron sulfide. The observed formation sequence of iron sulfide at high temperature was mackinawite → troilite → pyrrhotite → pyrite. The role of the different corrosion product layers in corrosion is discussed.